Electromagnetic shielding effectiveness of discontinuous metal fillers in carbon fiber reinforced epoxy composites - Ng, Zhihui. (2009)
Continuous carbon fiber reinforced epoxy matrix composite is an excellent electromagnetic interference shielding material. This project aims to explore the effect of the addition of metal fillers flakes and nickel powder into continuous carbon fiber reinforced epoxy matrix composite on its electromagnetic shielding effectiveness in the frequency range of 30 – 1000 MHz. Copper and nickel powders having different electrical conductivity and different magnetic permeability were used as metal fillers to investigate whether a higher electrical conductivity metal filler or a higher magnetic permeability metal filler is able to provide better electromagnetic shielding effect. The experimental results show that copper powder metal filler which is higher in electrical conductivity provides a better electromagnetic shielding effect where the dominant mechanism is believed to be electromagnetic reflection. Copper powder and powder flakes having different particle sizes were also used as metal fillers to investigate how electromagnetic shielding effectiveness is affected by different particle size of metal fillers used. Experimental results show that metal fillers with bigger particle size have a better electromagnetic shielding effect. Lastly, metal fillers of different volume fraction loadings were used and it was discovered that higher volume of metal fillers provides a better electromagnetic shielding effect.